PROBLEM-BASED LEARNING IN SOLUTION CHEMISTRY: ITS IMPACT ON CRITICAL THINKING AND ACADEMIC ACHIEVEMENT OF AIR FORCE ACADEMY CADETS - I Putu Bagus Mahendra; Isana Supiah YL (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aimed to analyze the effect of Problem-Based Learning (PBL) on critical thinking skills and academic achievement of Air Force Academy cadets in solution chemistry learning. The study employed a quasi-experimental design using a pretest–posttest control group design. The participants consisted of two classes, namely an experimental class taught using the PBL model and a control class taught using conventional learning. Data were collected using critical thinking questionnaires and chemistry achievement tests that have been validated and tested for reliability. The data were analyzed using descriptive statistics, normality and homogeneity tests, MANOVA, independent sample t-test, and N-Gain analysis. The results showed that the implementation of PBL had a significant simultaneous effect on critical thinking skills and academic achievement, as indicated by the multivariate test with p < 0.05. The univariate analysis also revealed significant differences between the experimental and control groups in critical thinking skills (p = 0.015) and academic achievement (p = 0.002). Furthermore, the N-Gain analysis indicated that the experimental class achieved higher improvement (0.2455) than the control class (0.1337), although both remained in the low category. These findings indicate that Problem-Based Learning contributes positively to improving cadets' critical thinking skills and academic achievement through active investigation, discussion, and contextual problem-solving activities. This study highlights the relevance of PBL implementation in military education, particularly in chemistry learning that requires conceptual understanding and analytical thinking skills.